2023
DOI: 10.1136/rapm-2022-104132
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating two approaches to the erector spinae plane block: an anatomical study

Abstract: Background and objectivesStudies show variable spread with thoracic erector spinae plane (ESP) injections. Injection sites vary from lateral end of the transverse process (TP) to 3 cm from the spinous process, with many not describing the precise site of injection. This human cadaveric study examined dye spread of ultrasound-guided thoracic ESP block at two needle locations.MethodsUltrasound-guided ESP blocks were performed on unembalmed cadavers. Methylene blue (20 mL, 0.1%) was injected in the ESP at the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Contrastingly, most studies investigating ESP injection spread have reported that lateral spread is limited by the lateral boundary of the erector spinae muscles, thereby contradicting Ivanusic's finding [10]. Recently, Harbell et al [16] used cadavers and reported that ESP injection, administered between the transverse processes, and not on the posterior surface of the transverse process, would be the key to attaining involvement of the ventral rami in the paravertebral space. Considering this, we administered a local anesthetic into the ESP between the T2 and T3 transverse processes, resulting in successful blockade of the intercostobrachial nerve, which implied the anterior spread of the local anesthetic by the ESP block.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Contrastingly, most studies investigating ESP injection spread have reported that lateral spread is limited by the lateral boundary of the erector spinae muscles, thereby contradicting Ivanusic's finding [10]. Recently, Harbell et al [16] used cadavers and reported that ESP injection, administered between the transverse processes, and not on the posterior surface of the transverse process, would be the key to attaining involvement of the ventral rami in the paravertebral space. Considering this, we administered a local anesthetic into the ESP between the T2 and T3 transverse processes, resulting in successful blockade of the intercostobrachial nerve, which implied the anterior spread of the local anesthetic by the ESP block.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, the likelihood of anterior spread (i.e., the ventral rami involvement) seen with the ESP block has been challenged [10,13,14]. Cadaver evaluations and MRI studies in healthy volunteers have shown that ESP injection spreads dye and local anesthetic over multiple paravertebral and epidural segments [10,[15][16][17][18]. In addition, some clinical studies have utilized ESP blocks for analgesia after breast and abdominal surgery and have reported promising results [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…(2) whether the allocation was hidden; (3) blinding of investigators and subjects; (4) blinding of study results; (5) completeness of the outcome data; (6) selective reporting of study results; and (7) other biases. Each included literature was evaluated in accordance with the abovementioned criteria and judged as "high risk of bias," "low risk of bias," or "unclear risk of bias."…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Midsternotomy incision is considered the primary source of pain, with the most severe pain occurring within the frst 24 h. Te sternal region is mainly sensed by the intercostal nerves [5]. Sensation in this region was mainly innervated by the anterior cutaneous branch of the intercostal nerve, which migrated from the intercostal nerve in the paraspinal region [6]. Transverse thoracic muscle plane (TTMP) block is a blocking technique developed in recent years.…”
Section: Introductionmentioning
confidence: 99%